Successive energy ratios in medium- and heavy-mass nuclei as indicators of different kinds of collectivity - Bonatsos, D; Skouras, L; Rikovska, J (1991)
The systematics of energy ratios of successive levels of collective bands in medium- and heavy-mass even-even nuclei are studied. A measure of their deviation from the vibrational and rotational limiting values is found to have different magnitude and angular momentum dependence in the vibrational, -unstable and rotational regions. The usefulness of this new criterion for distinguishing between different kinds of collective behavior is demonstrated in the case of intruder and octupole bands. © 1991 The American Physical Society.